2018
DOI: 10.1103/physrevb.98.245146
|View full text |Cite
|
Sign up to set email alerts
|

Charge disproportionation of Mn 3d and O 2p electronic states depending on strength of pd hybridization in

Abstract: The charge disproportionation of Mn 3d and O 2p electronic states was investigated in two (LaMnO3)2(SrMnO3)2 superlattices using the resonant x-ray scattering technique. The superlattices show significantly different conductivity even though the same composition. The large modulation of the Mn 3d electronic state was observed in the insulating sample, however the charge disproportionation and magnetic modulation of O 2p were shown in the semiconductive sample. It is suggested that the charge modulation appears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…While conventional metallic plasmons have been observed in multiple strongly correlated transition metal oxides, note that theoretical studies have revealed the interaction of both short- and long-range correlations in Mott insulating systems that can produce unconventional plasmons known as “correlated plasmons” which possess multiple ordered photon energies . These correlated plasmons have been experimentally observed in niobates, cuprates, and topological materials such as Bi 2 Se 3 , where charge-spin coupling plays an important role in the formation of correlated plasmons. ,, Meanwhile, orbital hybridization between the metallic 3d and oxygen 2p orbitals has been pivotal in accounting for multiple quantum phenomena in strongly correlated systems and their role in mediating the formation of plasmons remains largely an unchartered research frontier that requires further investigation. Moreover, as correlated plasmons are intimately related to long-range charge correlations, , the detection of these unconventional plasmons holds the potential to reveal valuable insights into the underlying mechanisms that result in their formation.…”
Section: Introductionmentioning
confidence: 99%
“…While conventional metallic plasmons have been observed in multiple strongly correlated transition metal oxides, note that theoretical studies have revealed the interaction of both short- and long-range correlations in Mott insulating systems that can produce unconventional plasmons known as “correlated plasmons” which possess multiple ordered photon energies . These correlated plasmons have been experimentally observed in niobates, cuprates, and topological materials such as Bi 2 Se 3 , where charge-spin coupling plays an important role in the formation of correlated plasmons. ,, Meanwhile, orbital hybridization between the metallic 3d and oxygen 2p orbitals has been pivotal in accounting for multiple quantum phenomena in strongly correlated systems and their role in mediating the formation of plasmons remains largely an unchartered research frontier that requires further investigation. Moreover, as correlated plasmons are intimately related to long-range charge correlations, , the detection of these unconventional plasmons holds the potential to reveal valuable insights into the underlying mechanisms that result in their formation.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly studied are LaMnO 3 |SrMnO 3 superlattices, where various magnetic and electronic ground states across the metal-insulator transition can be tuned [10,[46][47][48][49][50]. This is achieved by varying their period or component ratio [47,48,51], which is a way to modulate the tunneling of e g electrons across the interface [48]; orbital [52] and charge [53] order were also reported. More exotic phenomena, including correlated topological states, may be expected when passing from the (001) orientation to the (111) orientation, because of the large polarity and a peculiar symmetry-driven epitaxial strain [54,55].…”
Section: Introductionmentioning
confidence: 99%
“…LaMnO 3 (LMO) films are attracting extensive attention as an indispensable component part in many artificially constructed heterostructures which exhibit extraordinary interfacial phenomena, such as exchange bias in LMO/LaNiO 3 superlattices, 1 charge transfer in LMO/BiFeO 3 heterostructures, 2 charge disproportionation in LMO/SrMnO 3 superlattices, 3 ferromagnetic coupling, and half-metallicity in LMO/SrTiO 3 (STO) heterostructures. 4 In general, the ferromagnetic state, paramagnetic state, and antiferromagnetic state are known as the conventional magnetic states in magnetic materials.…”
Section: ■ Introductionmentioning
confidence: 99%